Investigations of selected ethnobotanicals for their potential uses in reproduction and fertility management. - Gonzaga-Leong-on, Ma. Socorro C.
This study was designed to screen, using mice as models, the crude methanolic extra of the three (3) most commonly prescribed plants by Traditional Birth Attendants (TBAs) in Guimaras, Antique and Iloilo for bioactivities related to reproduction such as precoital and postcoital antifertility and abortifacient testings, which might be used as alternatives to modern contraceptives drugs for humans. Other biological activities such as analgesis and antimicrobial activities were also determined. To determine safety for human use, cyctotoxicity assay, mutagenicity, and teratogenicity test were conducted. The plants used were Albutra (Arcangelisia flava), Bita (Alstonia scholaris) and Lampunaya (Coleus blumei). Results showed that Bita and Lampunaya can prevent ovulation as shown by the negligible numbers of of corpora lutea when administered at 5 mg/20 g body weight of mice 7 days before mating. In postcoital activity testing, all the crude methanolic plant extracts (Albutra, Bita, and Lampunaya) did not prevent implantation but caused early sbortifacient effects when fed at 5 mg/20g body weight to mice. Bita and Lampunaya still exhibited abortifacient effects administered postcoital up to day 5 of pregnancy. Bita, Lampunaya and Albutra (only when taken in after mating) produced uterotrophic effect which resulted n zero gestation index and atrophy of uterus. All the crude methanolic plant extracts had no abortifacient activities when administered at day 10 of pregnancy in mice. Using Paper Disc Diffusion Method, all the plant extracts have antibacterial activities against Escherichia coli, Pseudomonas aeruginosa, Bacillus sublitis and Staphyloccocus aureus except Lampunaya that had no antibacterial activity against B. sublitis. All the methanolic plant extracts had antifungal activties against Candida albicans. The study also showed that all plants extracts have analgesic activities using acetic acid induced writhing assay. Dominant Lethal Test for teratogenicity showed that all plant extracts are not teratogenic. No gross abnormalities were found in mice at birth. Mutagenicity test showed that the extracts are not capable of inducing polychromatic micronucleated erythrocyes. This tudy found out that Albutra, Bita, Lampunaya san be used as abortificient agents when administered at psotcoital and at day 5 of pregnancy among mice. Bita and Lampunaya can be an antifertility agent, specifically, they can prevent ovulation. The crude methanolic extracts of all plants can be used as antibacterial and antifungal agents, and as an analgesis. All plant extracts are not teratogenic, non mutagenic and nontoxic. The study confirmed the uses of Albutra, Bita and Lampunaya in the rural areas of Iloilo, Guimaras and Antique.